2021
DOI: 10.1002/ffj.3669
|View full text |Cite
|
Sign up to set email alerts
|

Identification of aroma compounds in raw and cooked broccoli

Abstract: Broccoli is characterized by its specific flavor, which is the reason it is not tolerated by some consumers. The role of aroma in flavor is crucial; however, the characteristics of aroma‐active components in broccoli are still unclear. Solvent‐assisted flavor evaporation (SAFE) with the aid of solid‐phase microextraction (SPME) and fractionation using solid phase extraction (SPE), followed by different chromatography‐mass spectrometry approaches (GC‐MS, GC‐MS/MS, GC×GC‐ToFMS) were used to identify the compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Although the VOCs in Brassica vegetables have been widely studied [ 38 , 39 , 40 , 41 ], in this study, the profile of broccoli leaves was analysed for the first time. Previous studies showed that the analysis of fresh vegetables resulted in a high abundance of sulphur compounds, including isothiocyanates derived from glucosinolates, which are responsible for a cabbage-like aroma [ 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the VOCs in Brassica vegetables have been widely studied [ 38 , 39 , 40 , 41 ], in this study, the profile of broccoli leaves was analysed for the first time. Previous studies showed that the analysis of fresh vegetables resulted in a high abundance of sulphur compounds, including isothiocyanates derived from glucosinolates, which are responsible for a cabbage-like aroma [ 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…An important compound responsible for sulphur aroma is dimethyl sulphide. Although its abundance was low in BLP and did not differ between pastas B2.5 and 5, this compound was previously reported to be one of the key odorants in Brassica vegetables [ 41 ]. Importantly, the odour threshold of dimethyl sulphide is very low and was estimated as 0.0008–0.03 and 0.0003–0.16 mg kg −1 in water and air, respectively [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The determination of ITCs with GC-MS has been employed [104][105][106][107][154][155][156]. For the analysis of volatile ITCs, the eco-friendly technique of Solid Phase Microextraction (SPME) in conjunction with GC-MS has been also proposed [157][158][159][160][161]. A method employing GC-MS with a pre-column derivatization step has been also developed by Latxague et al [26].…”
Section: Gas Chromatography/mass Spectrometrymentioning
confidence: 99%